Survey of damage mechanisms on PVD coated HSS hobs used in Swedish gear manufacturing industry - Gerth, J; Larsson, M; Wiklund, U (Tribologia - Finnish Journal of Tribology, 2011)
Gear hobbing is widely used for production of cylindrical gears in the Swedish transmission industry. The hob, usually consisting of a homogenous HSS (High Speed Steel) body coated with a ceramic PVD (Physical Vapour Deposition) coating, is designed for regrinding and recoating several times without affecting its cutting geometries. Efficient usage of the tool, considering production costs and gear quality, requires reconditioning before wear starts to affect the gear quality negatively and certainly before tool wear renders reconditioning impossible. Hobs of today generally lack in reliability, making it difficult to judge when they have to be taken out for reconditioning. This work presents a survey of wear as observed on today’s state of the art hobs used by Swedish gear manufactures. It aims to identify damage mechanisms and the common problems in order to enable future production of more reliable hobs. The tools were temporarily borrowed from the production and the analyses were made non-destructively using optical microscopes. This was complemented by destructive cross- sectional analysis on two of the hobs. Wear was most commonly located on the rake faces and the cutting edges of the cutting teeth. It mainly propagates by discrete fractures which appear to originate at local defects in the coating or at the interface. High intrinsic stress in the coating likely promotes coating spallation and accelerates the wear of the cutting edge.